Penafsiran QS Al Maun Dalam Tafsir Al Ibriz Karya KH.Bisri Musthofa : Etika Sosial Pesantren - Fawwaz, Muhammad; Refansyah, M Yoga; Pratama, Jecky (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren, 2025)
This paper examines the interpretation of Surah al-Ma'un in the Tafsir Al-Ibriz by KH. Bisri Musthofa and its relevance to the formation of social ethics in Islamic boarding schools (pesantren). Through a literature study and content analysis approach, this research finds that KH. Bisri Musthofa understands Surah al-Ma'un as a critique of religious practices that are merely ritualistic without social sensitivity. In his interpretation, values such as concern for the poor, empowerment of the weak, and rejection of stinginess and ostentation become the ethical foundations for students and the Islamic boarding school community. This interpretation not only emphasizes theological aspects but also builds social awareness contextual to the lives of rural Javanese communities. This study concludes that KH. Bisri Musthofa's interpretation makes a significant contribution to strengthening the tradition of Islamic boarding school social ethics oriented towards humanity, solidarity, and social benefit.